Bioethics and Person in Peter Singer's Work - Polo Santillan, Miguel (2004)
This article deals with Peter Singer's argument about a distinction hernakes between human beings as rnernbers of human species, and personsas rational subjects. Only the latter would ha ve rights, including the rightto life, an issue which rises bio-ethical questions and has no fewdetractors.